Nutritional Content of Functional Herbal Drinks Made from Palm Sugar Powder and Spice Powder - Sudiarto, Sudiarto; Saleh, Rosmiati; Sawab, Sawab; Widowati, Indar (Universitas Pattimura, 2022)
In all regions of the world, including Indonesia, there is a change in the patterns of disease from infectious diseases to degenerative diseases and non-communicable diseases. The COVID-19 pandemic has also raised awareness of the need to continually strengthen the immune system. Increasing the body's resistance can benefit from the use of traditional herbs with medicinal capabilities. Some biological plants such as red ginger, alang-alang root, galangal which are known to the public for their spices, can become herbal drinks when formulated with the addition of palm sugar. These three plants have been studied on a laboratory scale to identify nutrients and bioactive compounds that are beneficial for health. The purpose of this study was to determine the nutritional content of functional herbal drink products made from palm sugar and spice powder (red ginger, alang-alang root, and galangal). The research method was carried out using hedonic organoleptic tests on 3 prepared formulas, phytochemical screening, and proximate test (nutritional content) The results of the organoleptic test showed that respondents preferred a formula containing ginger (500 g), alang-alang root (200 g), galangal (100 g,) and palm sugar (200 g). Phytochemical screening showed each component (ginger, galangal, alang-alang, palm sugar, and the developed formula) was positive for flavonoids and alkaloids. Only ginger was positive for tannins, all negative components were steroids/triterpenoids and only galangal was positive for saponins. Carbohydrate, protein, fat, moisture, and ash contents were 4.49%, 4.38%, 3.95%, 47.68%, and 9.76%. The results showed that a functional herbal drink made from palm sugar and spices has health benefits and the potential to be a functional drink.